Does sustainability matter in the global beer industry? Bibliometrics trends in recycling and the circular economy - Ravanal, María Cristina; Doussoulin, Jean Pierre; Mougenot, Benoit (Frontiers in Sustainable Food Systems, 2024)
It is commonly known that the beer industry, like many other companies in the food sector, has been encouraged to improve their sustainability and waste management requirements. This study intends to fill the gap referring to the Brewery Industry’s impact on academics from 1972 to 2022 related to recycling and waste management issues. The above research utilizes bibliometric analysis via Biblioshiny and the Scopus publications database, as well as an online interface for Bibliometrix analysis. For studying the Global Brewery Industry literature, this method offers a viable alternative to traditional bibliometric analysis. Among the findings we can mention are that most Brewery Industry inquiries were distributed by the “Bioresource Technology” and the most globally cited document is the book titled “Brewing: Science and Practice” written by De Briggs in 2004. European countries such as Italy, Spain and Portugal hold a strong academic collaboration with the Americas (mainly Canada, United States and Brazil). Another interesting finding indicates that the circular economy and recycling are not very present topics in the scientific literature, maybe because sustainability is a subject of recent discussion and study in the brewing industry.